Sosialisasi Penguatan Literasi Digital bagi Pelajar untuk Menangkal Hoaks dan Provokasi di Media Sosial - Kampono Imam Yulianto; Mayang Riyantie (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The community service program was aimed at improving digital literacy for high school and vocational students in Jakarta so that they would not easily be provoked by various issues circulating on social media considering that recently many students participated in demonstrations which turned anarchic due to calls from unverified accounts online. The team used the method of interactive online socialization with material presentations, discussions, and quizzes to maximize student participation in the learning process. Evaluations carried out on this program showed very significant increases in student knowledge levels, especially regarding their ability to identify hoax news, recognize provocative narratives, and understand the social risks that can arise from misusing digital media. Changes in attitudes were also seen more critically and wisely among students when disseminating information as well as being careful even fostering new awareness about acting as an agent of digital literacy within their environment through re-disseminating acquired knowledge plus creating positive content on social media. Although implemented online, it was effective, inclusive, and relevant to the needs of students in this digital era opening up opportunities for the sustainability of similar implemented programs supporting a healthy productive ecosystem digitally among students.